PARASOCIAL INTERACTIONS FOR ENHANCING PURCHASE DECISIONS: PERSPECTIVES OF SERVICE DOMINANT LOGIC THEORY - Nilna Muna; Gede Crisna Wijaya; Putu Yuli Widya Astuti (Jurnal Ilmiah Manajemen & Bisnis, 2022)
The COVID-19 crisis is sweeping the world and affecting our lives, including consumer purchasing habits, preferences, and decisions. The survey, involving 251 respondents from Bali, Indonesia, examined how the pandemic affected Bali's purchasing decisions and consumer preferences. This paper aims to explore the impact of social media on consumer purchasing decisions, more specifically, examining the influence of social media on online shopping during the COVID-19 outbreak rooted in the service dominant logic (SDL) theory. Four hypotheses were developed and tested in the framework of a sample of 251 respondents from the Bali province. The proposed hypothesis was tested using AMOS 23 to perform structural equation modeling. The findings of this study suggest the critical role of social media interactivity in the two folds. First, parasocial interactions proved to be mediators of social media interactivity in improving purchasing decisions. Second, parasocial interaction has the potential to influence the decision-making of product purchasing preferences.